(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article analyzes the main ways of enhancing consumer experience through digital tourism services. The impact of modern technologies—such as artificial intelligence, mobile applications, virtual and augmented reality (VR/AR), and digital platforms—on the tourism sector is examined. The key factors shaping consumer experience are considered, and strategies for their improvement are developed. The article also analyzes the prospects for the development of this direction in the context of Uzbekistan, along with the role of modern technologies in enhancing consumer experience through digital tourism services.